OXIDATIVE STRESS IN ALZHEIMER’S DISEASE–EVALUATING THE AMYLOID BETA HYPOTHESIS - G., SWETHA; RAJ, ANJALI; TABASSUM, SANIYA; CHHAKCHHUAK, DOUGLAS ZORINMAWIA (International Journal of Current Pharmaceutical Research, 2021)
Dementia is defined by the debilitation of cognition and behavior of individuals more than 65 y. Alzheimer's disease (AD) is the most pervasive pervasive form of dementia, afflicting around 47 million individuals worldwide. Oxidative damage is a significant component in the pathophysiology of Alzheimer's disease (AD). Assessment of Alzheimer's disease mind has shown a lot of oxidative harm, related with both trademark pathologies (senile plaques and neurofibrillary tangles) just as in typical seeming pyramidal neurons. By the by, the process that eventually causes disruption of redox balance and furthermore the origin of the free radicals are as yet hazy. There is likewise the accessibility of proof that oxidative stress may enhance the conglomeration and production of Aβ and furthermore help the polymerization just as phosphorylation of tau, subsequently making a pernicious cycle that invigorates the development and even commencement of Alzheimer's. These neurotic trademarks have complex proportional collaborations with cholinergic abrasions. This review may give complemental data for understanding the relationship between oxidative stress, amyloid plaques, tau proteins and cholinergic system in processing of AD.